The use of platelet-rich and platelet-poor plasma to enhance differentiation of skeletal myoblasts: Implications for the use of autologous blood products for muscle regeneration - Miroshnychenko, O.; Chang, W.-T.; Dragoo, J. L. (The American Journal of Sports Medicine, 2017)
Background: Platelet-rich plasma (PRP) has been used to augment tissue repair and regeneration after musculoskeletal injury. However, there is increasing clinical evidence that PRP does not show a consistent clinical effect. Purpose/Hypothesis: This study aimed to compare the effects of the following non-neutrophil-containing (leukocyte-poor) plasma fractions on human skeletal muscle myoblast (HSMM) differentiation: (1) PRP, (2) modified PRP (Mod-PRP), in which transforming growth factor ß1 (TGF-ß1) and myostatin (MSTN) were depleted, and (3) platelet-poor plasma (PPP). The hypothesis was that leukocyte-poor PRP would lead to myoblast proliferation (not differentiation), whereas certain modifications of PRP preparations would increase myoblast differentiation, which is necessary for skeletal muscle regeneration. Study Design: Controlled laboratory study. Methods: Blood from 7 human donors was individually processed to simultaneously create leukocyte-poor fractions: PRP, Mod-PRP, PPP, and secondarily spun PRP and Mod-PRP (PRPss and Mod-PRPss, respectively). Mod-PRP was produced by removing TGF-ß1 and MSTN from PRP using antibodies attached to sterile beads, while a second-stage centrifugal spin of PRP was performed to remove platelets. The biologics were individually added to cell culture groups. Analysis for induction into myoblast differentiation pathways included Western blot analysis, reverse-transcription polymerase chain reaction, and immunohistochemistry, as well as confocal microscopy to assess polynucleated myotubule formation. Results: HSMMs cultured with PRP showed an increase in proliferation but no evidence of differentiation. Western blot analysis confirmed that MSTN and TGF-ß1 could be decreased in Mod-PRP using antibody-coated beads, but this modification mildly improved myoblast differentiation. However, cell culture with PPP, PRPss, and Mod-PRPss led to a decreased proliferation rate but a significant induction of myoblast differentiation verified by increased multinucleated myotubule formation and myosin heavy chain expression (mean 8-fold change in mRNA level; P < .05), which was comparable with 2% horse serum, the positive control. Conclusion: PPP and leukocyte-poor PRP preparations subjected to a second spin to remove the platelets led to induction of myoblast cells into the muscle differentiation pathway, whereas unmodified leukocyte-poor PRP led to myoblast proliferation. Clinical Relevance: